2000
DOI: 10.1177/1359104500005004007
|View full text |Cite
|
Sign up to set email alerts
|

Bereavement: A Framework for those Working with Children

Abstract: This article aims to describe psychological factors which help or hinder coping with bereavement in childhood. Children can and do cope with the death of those close to them if they know what is happening and have the appropriate support to cope. However, children suffering from loss are likely to be in the care of adults who are also grieving and there is a need to support the adults and to mobilize other resources for the child. We discuss the timing and appropriateness of interventions from all those workin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…However, research by Christ (2000) has shown that when the surviving parent and their children talk about the parent's death, children are more likely to have better psychological outcomes. Likewise, it has been shown that children's coping is enhanced when they are provided with a clear and honest explanation about what has happened (Melvin & Lukeman, 2000). Through these conversations, children are helped to begin to process both cognitively and emotionally what has happened and thus equipped to start writing their last chapter which has meaning and substance.…”
Section: Introductionmentioning
confidence: 98%
“…However, research by Christ (2000) has shown that when the surviving parent and their children talk about the parent's death, children are more likely to have better psychological outcomes. Likewise, it has been shown that children's coping is enhanced when they are provided with a clear and honest explanation about what has happened (Melvin & Lukeman, 2000). Through these conversations, children are helped to begin to process both cognitively and emotionally what has happened and thus equipped to start writing their last chapter which has meaning and substance.…”
Section: Introductionmentioning
confidence: 98%
“…In a familiar and supportive environment with a trusted adult, children are willing to discuss their fears and emotions about death. Using both developmental theories and clinical experience, clinical psychologists have suggested that providing children with additional information about death and the opportunity to make sense of the death of a loved one can act as moderating factors in a child's bereavement process (Melvin & Lukeman, ). Yet, when parents and teachers are asked their opinions about death education in the home and classroom, they often report feelings of discomfort around talking to children about death (McGovern & Barry, ).…”
mentioning
confidence: 99%
“…Over the past two decades, bereavement services have begun to emerge as a significant form of specialised support for children and young people (referred to generically in this paper as 'children'), and there is an increasing UK (as opposed to US) literature about the practical issues involved (Stokes et al, 1999;Melvin & Lukeman, 2000;Worswick, 2000); the types of interventions that services use (Stokes & Crossley, 1996;Potts, Farrell & OToole, 1999;Nugus Challenges in evaluating childhood bereavement services 1 The uncertain nature of childhood bereavement…”
Section: The Complexity Of the Child Bereavement Service Contextmentioning
confidence: 99%